Father Abraham's many children : the Bible in a world of religious difference - Mayfield, Tyler D., 1980- (Grand Rapids, Michigan : William. B. Eerdmans Publishing Company, 2022)
"A theology of Christian engagement with religious diversity today through in-depth readings of marginalized characters in the book of Genesis"--
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc; Christianity and other religions